The tender vine - Heitzmann, Kristen (Heitzmann, Kristen. Diamond of the Rockies, 2002)
"Carina DiGratia Shepard ... starts anew in the California vineyard of her youth. With Quillan bent on proving his devotion, Carina dares to open her heart to this rogue husband who has brought both pain and passion-and together they attempt to resurrect the tattered remains of their relationship and create a marriage where love truly reigns."--Back cover.